Conductive paste for HJT solar cell and preparation method thereof

By synthesizing the sub -micron copper wire and coin -based copper micron stick powder in the HJT solar battery, and using silver iodide to form a original nano -silver, solve the problem of high contact resistance and wire resistance in HJT solar battery conductive plasma, realized low cost, and low -cost Optimization and performance optimization.

CN119381083APending Publication Date: 2025-01-28SUZHOU JOINT RESEARCH MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310910344.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

During the metallization process, HJT solar cells cannot use high-temperature sintering technology to form ohmic contacts, and silver paste is used and costly, so it is necessary to reduce contact resistance and line resistance while reducing material costs.

Method used

By dissolving copper salt, glucose, and fat amine in the water, react to generate a sub -micron copper line dispersing solution, and synthesize the copper micronic powder powder of the coin bag through chemical plating method. Purch.

Benefits of technology

The low cost of HJT solar battery conductive plasma is implemented, the contact resistance and wire resistance are reduced, and the string resistance and filling factors of the battery film are optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381083A_ABST
    Figure CN119381083A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of conductive paste for an HJT solar cell, which comprises the following steps: 1) dissolving copper salt, glucose and fatty amine in deionized water, putting into a hydrothermal tank for reaction, cooling to room temperature, cleaning and filtering to obtain a copper nanowire dispersion liquid; 2) adding a dispersing agent and a reducing agent into the copper nanowire dispersion liquid, uniformly stirring, dropwise adding a silver nitrate aqueous solution into the copper nanowire dispersion liquid, continuously stirring, reacting, cleaning, centrifugally separating and drying to obtain silver-coated copper microrod powder; and 3) pre-mixing the epoxy resin carrier, the thermoplastic resin carrier, the curing agent, the diluent and the auxiliary agent, then adding the silver-coated copper microrod powder, the spherical silver powder and the silver iodide powder, dispersing and homogenizing on a three-roller machine, and obtaining the conductive paste for the HJT solar cell when the fineness of a scraper is less than 10 microns. According to the invention, the contact resistance and the line resistance are reduced in the HJT metal, and the cost of the HJT slurry is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar cell metallization, and in particular to a conductive paste for HJT solar cells and a preparation method thereof. Background Art

[0002] Compared with traditional P-type silicon solar cells, N-type silicon cells have advantages such as longer carrier diffusion length and longer minority carrier lifetime. Silicon heterojunction solar cells (HJT) are based on N-type silicon technology and combined with thin-film solar cell technology. They have the advantages of fewer manufacturing processes, high efficiency, high bifaciality, low attenuation and low temperature coefficient, and strong weak light power generation capabilities.

[0003] The amorphous silicon layer and TCO film layer of HJT solar cells have a preparation process temperature below 250°C. During the metallization process, it is impossible to use the high-temperature sintering process of silver powder and glass phase to achieve ohmic contact. Instead, a low-temperature curing method is used to form metallized grid lines. Screen-printed conductive silver glue is a key material for surface metallization of HJT solar cells. Silver powders and silver and ITO film layers are bonded with organic resin phases, which requires good conductivity and ohmic contact properties, while ensuring good adhesion and printing properties. In addition, compared with PERC and TOPCon cells, silver paste usage is large and costly, accounting for more than 50% of the non-silicon wafer cost of the cell, and faces huge cost reduction pressure. Therefore, silver-clad copper technology is an important route to reduce silver usage.

[0004] In HJT conductive paste, the gate line resistance is usually optimized by grading flaky powder and spherical powder. The stacking resistance of flaky powder is smaller than the contact tunneling resistance between spherical powders. However, a large amount of flaky powder will cause the bottom of the plate to be hollow at the pyramid interface with the silicon wafer surface, increase the contact resistance, and reduce the filling factor. Compared with flaky powder formed by processes such as ball milling, rod-shaped or linear powder can reduce or avoid contact suspension and have good line resistance. Silver nanowire synthesis is now very mature, but when used in paste, too large a wire diameter ratio will bring difficulties to screen printing. Therefore, it is necessary to make targeted improvements to these problems. Summary of the invention

[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a method for preparing a conductive paste for HJT solar cells, which can reduce the contact resistance and line resistance of HJT metal and reduce the cost of HJT paste.

[0006] To achieve the above technical objectives, the technical solution of the present invention is: a method for preparing a conductive paste for HJT solar cells, comprising the following steps:

[0007] 1) Dissolve copper salt, glucose and fatty amine in deionized water, put into a water heating tank with Teflon lining, react at 100-140° C. for 6-12 hours, cool to room temperature, wash and filter with deionized water to obtain a submicron copper wire dispersion;

[0008] 2) adding a dispersant and a reducing agent to the submicron copper wire dispersion in step 1), stirring evenly, and then dripping a silver nitrate aqueous solution therein, stirring continuously, and the dripping and reaction time is 2 to 6 hours in total, washing, centrifuging and drying to obtain a silver-coated copper micron rod powder;

[0009] 3) premixing the epoxy resin carrier, the thermoplastic resin carrier, the curing agent, the diluent and the auxiliary agent, adding the silver-coated copper microrod powder obtained in step 2), and then adding the spherical silver powder and the silver iodide powder, dispersing and homogenizing on a three-roll mill, and obtaining the conductive paste for the HJT solar cell when the scraper fineness is less than 10 μm.

[0010] Optionally, the copper salt in step 1) is a combination of one or more of copper chloride, copper nitrate and copper sulfate; and the fatty amine is one of dodecylamine, tetradecylamine and octadecylamine.

[0011] Optionally, the molar concentration of the silver nitrate aqueous solution in step 2) is 2-4 mol / L, the silver mass equivalent is 0.5-2 times the copper mass equivalent in the submicron copper wire dispersion; the dispersant is one of PVP, PEO, and PEG; and the reducing agent is one of ascorbic acid and glucose.

[0012] Optionally, the epoxy resin carrier is one of phenolic epoxy, DCPD epoxy, and bisphenol F epoxy; the thermoplastic resin carrier is one or more of TPU resin, phenoxy resin, and chloroacetic acid resin; the curing agent is a latent curing agent, including a combination of one or more of blocked isocyanate curing agents, imidazole curing agents, dicyandiamide curing agents, boron trifluoride complexes, and antimony hexafluoride complexes.

[0013] Optionally, the silver-coated copper microrod powder obtained in step 2) has a length of 3 to 20 μm and a diameter of 100 to 400 nm.

[0014] Optionally, in step 3), the spherical silver powder has a particle size of 2 to 8 μm.

[0015] Optionally, the diluent is one or more of alcohol ester dodecaned, ethylene glycol butyl ether acetate, ethylene glycol ethyl ether acetate, ethylene glycol dibutyl ether, and ethylene glycol butyl ether.

[0016] Optionally, the auxiliary agent includes a thixotropic agent and a leveling agent; the thixotropic agent is one or more of fumed silica, polyamide wax, and polyamide-modified hydrogenated castor oil; and the leveling agent is dimethyl silicone oil.

[0017] The present invention also provides an electronic paste for HJT solar cells. The conductive paste for HJT solar cells is prepared by the above-mentioned preparation method. The prepared conductive paste for HJT solar cells comprises, by weight percentage: 30-65wt% of silver powder, 30-65wt% of silver-coated copper microrod powder, 0.5-2wt% of silver iodide, 1-5wt% of epoxy resin, 1-5wt% of thermoplastic resin carrier, 0.2-1wt% of curing agent, 1-3wt% of diluent, 0-0.3wt% of thixotropic agent and 0.1-0.3wt% of leveling agent.

[0018] The conductive paste for HJT solar cells of the present invention has the following beneficial effects: using synthetic submicron copper wire as a seed, chemically plating to synthesize silver-coated copper microrods, which are used for HJT metal, have good line resistance and contact resistance, and silver iodide decomposes during the curing process to form in-situ nanosilver, which plays a role of low-temperature "sintering", further optimizing the battery cell string resistance and fill factor. In addition, the present invention also has the advantage of lower material cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The present invention is a flow chart of a method for preparing a conductive paste for HJT solar cells, including steps S1 to S3.

[0020] Figure 2 This is a SEM photograph of the silver-coated copper microrod powder obtained in step 2) of the preparation method of the present invention. DETAILED DESCRIPTION

[0021] The following describes the implementation of the present invention through specific embodiments, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific implementations, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0022] The conductive paste for HJT solar cells and the preparation method thereof of the present invention will be further described below in conjunction with specific examples and comparisons.

[0023] The preparation process of the conductive paste for HJT solar cells of the present invention is shown in Figure 1 , the specific steps are as follows:

[0024] First, copper salt, glucose and fatty amine are dissolved in deionized water, put into a water heating tank with Teflon lining, reacted at 100-140°C for 6-12 hours, cooled to room temperature, washed and filtered with deionized water to obtain a submicron copper wire dispersion; the copper salt can be a combination of one or more of copper chloride, copper nitrate and copper sulfate; the fatty amine is one of dodecylamine, tetradecylamine and octadecylamine.

[0025] Subsequently, a dispersant and a reducing agent are added to the obtained submicron copper wire dispersion, and after being stirred evenly, a silver nitrate aqueous solution is added dropwise thereto, and the stirring is continued. The dropping and reaction time is 2 to 6 hours in total, and silver-coated copper micron rod powder is obtained after washing, centrifugal separation and drying. The molar concentration of the silver nitrate aqueous solution is 2 to 4 mol / L, and the mass equivalent of silver is 0.5 to 2 times the mass equivalent of copper in the submicron copper wire dispersion. The dispersant can be one of PVP, PEO and PEG; and the reducing agent is one of ascorbic acid and glucose.

[0026] The obtained silver-coated copper microrod powder is as follows Figure 2 As shown, the silver-coated copper microrod powder has a length of 3 to 20 μm and a diameter of 100 to 400 nm.

[0027] Then, the epoxy resin carrier, the thermoplastic resin carrier, the curing agent, the diluent and the auxiliary agent are premixed. The epoxy resin carrier can be one of phenolic epoxy, DCPD epoxy and bisphenol F epoxy; the thermoplastic resin carrier can be one or more of TPU resin, phenoxy resin and chlorovinyl resin; the curing agent is a latent curing agent, which can be a combination of one or more of blocked isocyanate curing agent, imidazole curing agent, dicyandiamide curing agent, boron trifluoride complex and antimony hexafluoride complex. The diluent can be one or more of alcohol ester dodecahydrate, ethylene glycol butyl ether acetate, ethylene glycol ethyl ether acetate, ethylene glycol dibutyl ether and ethylene glycol butyl ether. The auxiliary agent includes a thixotropic agent and a leveling agent; the thixotropic agent can be one or more of fumed silica, polyamide wax and polyamide modified hydrogenated castor oil; the leveling agent is dimethyl silicone oil.

[0028] Silver-coated copper microrod powder, spherical silver powder with a particle size of 2 to 8 μm, and silver iodide powder are added. The final formula includes 30 to 65 wt% of silver powder, 30 to 65 wt% of silver-coated copper microrod powder, 0.5 to 2 wt% of silver iodide, 1 to 5 wt% of epoxy resin, 1 to 5 wt% of thermoplastic resin carrier, 0.2 to 1 wt% of curing agent, 1 to 3 wt% of diluent, 0 to 0.3 wt% of thixotropic agent and 0.1 to 0.3 wt% of leveling agent. The total mass fraction is 100%. The proportion of each component is reasonably distributed within its range, taking into account the conductive properties, printing properties and curing properties.

[0029] The mixture is dispersed and homogenized on a three-roll mill. When the scraper fineness is less than 10 μm, the conductive paste for HJT solar cells is obtained.

[0030] The present invention also provides an electronic paste for HJT solar cells prepared by the preparation method. In the final formula, the conductive paste for HJT solar cells comprises 30-65wt% of silver powder, 30-65wt% of silver-coated copper microrod powder, 0.5-2wt% of silver iodide, 1-5wt% of epoxy resin, 1-5wt% of thermoplastic resin carrier, 0.2-1wt% of curing agent, 1-3wt% of diluent, 0-0.3wt% of thixotropic agent and 0.1-0.3wt% of leveling agent, and the total mass fraction is 100%.

[0031] Example 1

[0032] A conductive paste for HJT solar cells is prepared by the following preparation method:

[0033] 1) Dissolve copper chloride, glucose and dodecylamine in deionized water, put into a water heating tank with a Teflon lining, react at 100° C. for 6 hours, cool to room temperature, wash and filter with deionized water to obtain a submicron copper wire dispersion;

[0034] 2) adding a dispersant PVP and a reducing agent ascorbic acid to the submicron copper wire dispersion in step 1), stirring evenly, and then dripping a silver nitrate aqueous solution therein, stirring continuously, and the dripping and reaction time is 6 hours in total, washing, centrifuging and drying to obtain a silver-coated copper micron rod powder;

[0035] 3) premixing DCPD epoxy resin, phenoxy resin, curing agent boron trifluoride complex, diluent ethylene glycol ethyl ether acetate and ethylene glycol dibutyl ether, and auxiliary agents polyamide modified hydrogenated castor oil and dimethyl silicone oil, adding the silver-coated copper microrod powder obtained in step 2), and then adding spherical silver powder and silver iodide powder, dispersing and homogenizing on a three-roll mill, and obtaining the conductive paste for HJT solar cells when the scraper fineness is less than 10 μm.

[0036] The conductive paste for HJT solar cells prepared by the above preparation method has the following components in proportion: 30wt% of silver powder, 58wt% of silver-coated copper microrod powder, 1wt% of silver iodide, 4wt% of DCPD epoxy, 3.3wt% of phenoxy resin, 0.4wt% of boron trifluoride complex, 1wt% of ethylene glycol ethyl ether acetate, 2wt% of ethylene glycol dibutyl ether, 0.1wt% of polyamide-modified hydrogenated castor oil and 0.2wt% of dimethyl silicone oil.

[0037] Comparative Example 1: The silver-coated copper microrod powder in Example 1 was replaced with flaky silver powder, and the other ingredients and processes were the same.

[0038] Example 2

[0039] A conductive paste for HJT solar cells is prepared by the following preparation method:

[0040] 1) Dissolve copper nitrate, glucose and tetradecylamine in deionized water, put into a water heating tank with a Teflon lining, react at 140° C. for 12 hours, cool to room temperature, wash and filter with deionized water to obtain a submicron copper wire dispersion;

[0041] 2) adding a dispersant PEG and a reducing agent glucose to the submicron copper wire dispersion in step 1), stirring evenly, and then dripping a silver nitrate aqueous solution therein, stirring continuously, and the dripping and reaction time is 4 hours in total, washing, centrifuging and drying to obtain a silver-coated copper microrod powder;

[0042] 3) premixing phenolic epoxy, TPU resin, blocked isocyanate curing agent, diluents ethylene glycol ethyl ether acetate and ethylene glycol butyl ether, and auxiliary agent dimethyl silicone oil, adding the silver-coated copper microrod powder obtained in step 2), and then adding spherical silver powder and silver iodide powder, dispersing and homogenizing on a three-roll mill, and obtaining the conductive paste for HJT solar cells when the scraper fineness is less than 10 μm.

[0043] The above preparation method is adopted to prepare the conductive paste for HJT solar cells, and the proportions of each component are: 40wt% of silver powder, 50wt% of silver-coated copper microrod powder, 1wt% of silver iodide, 3wt% of phenolic epoxy, 2.4wt% of TPU resin, 0.4wt% of blocked isocyanate curing agent, 1wt% of ethylene glycol ethyl ether acetate, 2wt% of ethylene glycol butyl ether, and 0.2wt% of dimethyl silicone oil.

[0044] Comparative Example 2: The silver iodide in Example 2 was replaced with nano silver powder, and the other components and processes were the same.

[0045] The above slurry was used to print the grid lines on the 166HJT cell, and then dried at 150°C for 5 minutes and cured at 190°C for 10 minutes. The efficiency test results are shown in Table 1.

[0046] Table 1 Efficiency test results of embodiments and comparative examples

[0047] EFF(%) Voc(V) Isc(A) FF(%) Rs(Ω) Example 1 23.79 0.7412 10.09 81.06 0.00264 Comparative Example 1 23.03 0.7416 9.82 79.99 0.00271 Example 2 23.96 0.7411 10.20 81.12 0.00233 Comparative Example 2 23.27 0.7412 10.08 80.67 0.00259

[0048] From the comparison between Example 1 and Comparative Example 1, it can be seen that Example 1 uses silver-coated copper microrod powder, and compared with Comparative Example 1 using flaky silver powder, the filling factor FF has a significant advantage, which is reflected in that although more copper components are introduced into the conductive filler, the series resistance is still lower than that of Comparative Example 1, showing good ohmic contact. From the comparison between Example 2 and Comparative Example 2, it can be seen that compared with the use of nanosilver particles, the use of in-situ silver generated during the silver iodide curing process is more conducive to reducing the series resistance and also more conducive to reducing the cost.

[0049] In summary, the preparation method of the conductive paste for HJT solar cells of the present invention uses a synthetic submicron copper wire as a seed, chemically plates and synthesizes silver-coated copper microrods for HJT metal, and has good line resistance and contact resistance. In addition, silver iodide decomposes during the curing process to form in-situ nanosilver, which plays a role of low-temperature "sintering" and further optimizes the cell string resistance and fill factor. In addition, the present invention also has a lower material cost. Therefore, the present invention effectively overcomes the shortcomings of the prior art and has a high industrial value.

[0050] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a conductive paste for HJT solar cells, characterized in that: The preparation method comprises the following steps: 1) Dissolve copper salt, glucose and fatty amine in deionized water, put into a water heating tank with Teflon lining, react at 100-140° C. for 6-12 hours, cool to room temperature, wash and filter with deionized water to obtain a submicron copper wire dispersion; 2) adding a dispersant and a reducing agent to the submicron copper wire dispersion in step 1), stirring evenly, and then dripping a silver nitrate aqueous solution therein, stirring continuously, and the dripping and reaction time is 2 to 6 hours in total, washing, centrifuging and drying to obtain a silver-coated copper micron rod powder; 3) premixing the epoxy resin carrier, the thermoplastic resin carrier, the curing agent, the diluent and the auxiliary agent, adding the silver-coated copper microrod powder obtained in step 2), and then adding the spherical silver powder and the silver iodide powder, dispersing and homogenizing on a three-roll mill, and obtaining the conductive paste for the HJT solar cell when the scraper fineness is less than 10 μm.

2. The method for preparing the conductive paste for HJT solar cells according to claim 1, characterized in that: In step 1), the copper salt is a combination of one or more of copper chloride, copper nitrate and copper sulfate; and the fatty amine is one of dodecylamine, tetradecylamine and octadecylamine.

3. The method for preparing the conductive paste for HJT solar cells according to claim 1, characterized in that: The molar concentration of the silver nitrate aqueous solution in step 2) is 2-4 mol / L, and the silver mass equivalent is 0.5-2 times the copper mass equivalent in the submicron copper wire dispersion; the dispersant is one of PVP, PEO, and PEG; and the reducing agent is one of ascorbic acid and glucose.

4. The method for preparing the conductive paste for HJT solar cells according to claim 1, characterized in that: The epoxy resin carrier is one of phenolic epoxy, DCPD epoxy, and bisphenol F epoxy; the thermoplastic resin carrier is one or more of TPU resin, phenoxy resin, and chloroacetic acid resin; the curing agent is a latent curing agent, including a combination of one or more of blocked isocyanate curing agents, imidazole curing agents, dicyandiamide curing agents, boron trifluoride complexes, and antimony hexafluoride complexes.

5. The method for preparing the conductive paste for HJT solar cells according to claim 1, characterized in that: The silver-coated copper microrod powder obtained in step 2) has a length of 3 to 20 μm and a diameter of 100 to 400 nm.

6. The method for preparing the conductive paste for HJT solar cells according to claim 1, characterized in that: In the step 3), the particle size of the spherical silver powder is 2 to 8 μm.

7. The method for preparing the conductive paste for HJT solar cells according to claim 1, characterized in that: The diluent is one or more of alcohol ester dodecaned, ethylene glycol butyl ether acetate, ethylene glycol ethyl ether acetate, ethylene glycol dibutyl ether, and ethylene glycol butyl ether.

8. The method for preparing the conductive paste for HJT solar cells according to claim 1, characterized in that: The auxiliary agent includes a thixotropic agent and a leveling agent; the thixotropic agent is one or more of fumed silica, polyamide wax, and polyamide-modified hydrogenated castor oil; and the leveling agent is dimethyl silicone oil.

9. A conductive paste for HJT solar cells, characterized in that: The conductive paste for HJT solar cells is prepared by the preparation method according to any one of claims 1 to 8; Measured by weight percentage, the prepared conductive paste for HJT solar cells includes: 30-65wt% of silver powder, 30-65wt% of silver-coated copper microrod powder, 0.5-2wt% of silver iodide, 1-5wt% of epoxy resin, 1-5wt% of thermoplastic resin carrier, 0.2-1wt% of curing agent, 1-3wt% of diluent, 0-0.3wt% of thixotropic agent and 0.1-0.3wt% of leveling agent.